2018
DOI: 10.1111/1346-8138.14314
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the use of topical retinoids in Asian acne patients

Abstract: Acne vulgaris is a common disease among people in Asia. International guidelines and treatment recommendations emphasize the central role of topical retinoids in the management of acne. However, topical retinoids remain underutilized in clinical practise, which may be in part due to fear of retinoid‐associated dermatitis/lack of experience, particularly in Asian patients. There is a perception that Asian skin has a greater tendency toward sensitivity compared with Caucasian skin. In our clinical experience, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 54 publications
(145 reference statements)
0
31
0
1
Order By: Relevance
“…Furthermore, patients seldom express their concerns and often do not ask questions about their diagnosis or treatment during consultations [ 31 , 32 ]. Educational interventions aim to empower patients in self-management of their disease [ 33 ] and an increase in disease knowledge is associated with better therapy adherence and higher patient satisfaction [ 34 , 35 ]. A recent US study on adults, adolescents and parents of children who had been prescribed an EAI revealed that 61% of participants desired more effective patient education and 47% desired more time dedicated to patient education during the physician visit to improve clinical anaphylaxis management [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients seldom express their concerns and often do not ask questions about their diagnosis or treatment during consultations [ 31 , 32 ]. Educational interventions aim to empower patients in self-management of their disease [ 33 ] and an increase in disease knowledge is associated with better therapy adherence and higher patient satisfaction [ 34 , 35 ]. A recent US study on adults, adolescents and parents of children who had been prescribed an EAI revealed that 61% of participants desired more effective patient education and 47% desired more time dedicated to patient education during the physician visit to improve clinical anaphylaxis management [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Topical retinoids are the mainstay for acne management, and also for maintenance therapy. 13 There is a need for early and efficacious treatment to minimize the potential impact of acne-associated PIH. 13 Beneficial action of topical retinoids on the dermis has further demonstrated their efficacy on secondary lesions of acne, i.e.…”
Section: Acne-induced Post-inflammatory Hyperpigmentationmentioning
confidence: 99%
“…13 There is a need for early and efficacious treatment to minimize the potential impact of acne-associated PIH. 13 Beneficial action of topical retinoids on the dermis has further demonstrated their efficacy on secondary lesions of acne, i.e. scarring and pigmentation.…”
Section: Acne-induced Post-inflammatory Hyperpigmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Também é fortemente recomendado o uso da combinação de PBO e Clindamicina para esse tipo de acne. Ainda segundo esse Guidelines, com força média de recomendação estão: o ácido azelaico, o peróxido de benzoíla, a combinação de antibiótico sistêmico com adapaleno, a associação de clindamicina e de tretinoína tópicas, além de retinoides tópicos 31 .…”
Section: Tratamento Da Acne Papulo-pustular Leve a Moderadaunclassified